Institutionalizing collaborative regional governance in organizationally thin regions—Regional development agencies and the neglect of social innovations - Kovanen, Sunna; Ulrich, Peter; Gailing, Ludger (Frontiers in Political Science, 2023)
This article compares one emerging and three established regional development agencies in rural regions in Germany as examples of collaborative governance for socially innovative regional development. We ask, firstly, how an emergent collaborative regional governance network can be institutionalized in the long term based on participatory mechanisms on several levels as well as between actors with different goals and values. Secondly, how an organizationally thin, rural context influences the governance network in steering the social innovation promotion and what kind of development for whom do different governance networks mobilize. The findings highlight that the institutionalization of collaborative governance is supported by funding and policies from upper scales and the model of regional development agency enhances the learning of collaborative governance between public institutions. However, the goal and beneficiaries of the development are mainly the classic economic actors, whereas transformative grassroots movements enhancing social innovation are largely ignored by public-driven collaborative governance.